Tracking Tumor Cells in Lymphatics in a Mice Xenograft Model by Magnetic Resonance Imaging - Ting Liu; Haijun Zhou; Rui Xia; Jichun Liao; Changqiang Wu; Hui Wang; Hua Ai; Feng Bi; Fabao Gao (Molecular Imaging)
To enrich our understanding of the mechanism of tumor lymphatic metastasis, we developed a model system for tracking metastatic tumor cells in the lymphatic system with cellular magnetic resonance imaging (MRI) in live mice to observe the interaction between tumor cells and the lymphatic system. Nude mice were inoculated subcutaneously with superparamagnetic iron oxide (SPIO)-labeled and unlabeled LOVO cells in the foot pad, groin, or axillary area. Serial 7 T MRI of the tumors and surrounding regions was performed in the following 2 weeks. After imaging, tumor tissues and regional lymph nodes were collected and subjected to immunohistologic analysis. T 2 /T 2 *-weighted MRIs showed the primary tumor growth and the draining lymphatic architecture, as well as the SPIO-labeled tumor cells metastasized into the regional lymph node at 8 days. MRIs also revealed information on sentinel lymph node mapping with high-resolution anatomic information. Histologic findings confirmed the in vivo MRI results and revealed lymphangiogenesis, angiogenesis, infiltration of macrophages, and expression of vascular endothelial growth factor C in tumor and draining lymph nodes as well. This technology provides a powerful tool for tracking SPIO-labeled cancer cells in the lymphatics by cellular MRI. There was a close relationship between tumor lymphatic metastasis and lymphangiogenesis.